Salubong - Dascil, Marianne Clariz Dagdagan; Dalena, Sari Raissa Ll. (2012)
"In the midst of the developing world, new values emerge as we continue to consume technology and modernity but the demands of our deeply rooted traditional values are still incessant. Salubong centers on this struggle between traditional and modern values. Guiding the film is the Domestication Theory of Technology that discusses how we design an environment where technology and the new values are adapted and domesticated depending on how we make meaning of them - based our existing belief and values. Another related theory is Symbolic Interactionism that deals with man's process of meaning-making. Set in the Laguna province during Holy Week, the film follows a young professional's stay in his mother's house after being away in Manila for a long time. Stuck with him is his stateside niece who is just as obstinate as he is in not taking part of the Lenten season at all. But as the days lead to the Salubong, an encounter with a childhood memorabilia brings the two closer in learning to open up to a rooted tradition and a forgotten passion."
Vita.
Undergraduate thesis (A.B. Film and Audio Visual Communication)--University of the Philippines, Diliman.
Keywords: Salubong (Short film).; Short films -- Philippines